PENGARUH HARGA, KUALITAS PELAYANAN, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SABANA FRIED CHICKEN - Wivirra Wietama; Febriansyah Febriansyah (Universitas Prof. Dr. Moestopo (Beragama), 2021)
This research aims to find out the influences between price, service quality and word of mouth to purchase decision of Sabana Fried Chicken. This research used quantitative approach through survey to 105 responses who have known or buying Sabana Fried Chicken. The sample selection technique has been done using non-probability sampling or purposive sampling. Data analysis technique is using multiplied linear regression analysis, though the hypothesis test uses test –t. Based on the result of hypothesis analysis shows that price has significant effect to purchase decision proved by t value 6,633 1,983, service quality has no significant effect to purchase decision proved by t value 1,058 1,983 and word of mouth has significant effect to purchase decision proved by t value 8,327 1,983